Unveiling the Effectiveness of Spencer technique and Activity Oriented Exercise Approach in subjects with Diabetic Adhesive Capsulitis-An Experimental Study. - Durga, N.; Anitha, A. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: This study aims to assess the influence of the Spencer technique and Activity Oriented Exercise Approach in managing pain and functional ability in subject withType-2 diabetes Adhesive capsulitis. As diabetic patients have high incidence of being diagnosed with Adhesive Capsulitis, the need for a better treatment for the pain and other symptoms are required. Methods: An experimental study design was conducted at Saveetha College of Physiotherapy that included female subjects aged 45 to 65 years with history of Type -2 diabetes, unilateral adhesive capsulitis, and shoulder pain and stiffness for over 4 months. Spencer group (n=22) treated with Spencer technique with active shoulder ROM exercises while the Activity Oriented Exercise Approach group (n=23) treated with individual tailored exercises of Activities of Daily living. Results: The post-test values of SPADI score (p-value < 0.0001) and joint measurements - abduction, internal rotation and external rotation of shoulder (p-value <0.0001) was statistically improved in both groups but Activity Oriented Exercise Approach group showed a greater and significant improvement in the outcomes than the Spencer group. Conclusion: From the results it was concluded that Activity Oriented Exercise Approach was effective in improving functional ability and range of motion in Type-2 diabetic adhesive capsulitis subjects. Future researches should be done with larger sample size and studies on absolute diagnostic test to identify the underlying mechanism of Adhesive Capsulitis.